Political Scepticism: A Panacea for the Nigerian Political Leadership Quagmire - Balogun, Babalola Joseph (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
The paper blames the ’Nigerian political misfortune on the ignorance of the masses. It argues that the gullibility of the Nigerian masses has not fared well on the political climate of the country. As a way of taming this political monster, the paper proposes a sceptical attitude among the masses. The proposed political scepticism is differentiated from a wholesome rejection of the possibility of good governance in the Nigerian polity; rather it is an attitude towards the establishment of a critical and rigorous intellectual basis for national political culture. This attitude, the paper maintains, is impossible without the internalization of an appropriate education, a form of education tailored towards the attainment of sustainable development in the political sphere. It is believed that the projected appropriation would help maintain a high standard of political proficiency among members of the political class by pruning the Nigerian politics of incompetent and selfish persons who have grown to an unbearable proportion.